2022
DOI: 10.15294/jstrp.v1i2.51512
|View full text |Cite
|
Sign up to set email alerts
|

Alpinia galanga Extract Inhibits MCF-7/HER2+ Cells by Inducing Apoptosis

Abstract: Background: Cancer is a disease caused by abnormal growth of body tissue cells. Cancer treatment strategy by induce apoptosis and inhibit proliferation. Aim: This research aims to examine the anticancer effect of Alpinia galanga extract on MCF-7/HER2+ breast cancer cells.  Method: The MTT Assay cytotoxic test was carried out to determine the growth inhibitory activity. Apoptotic assay to determine the activity of compounds in apoptosis, as well as through a structural approach utilizing various vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Genus Alpinia terutama dikenal sebagai tanaman dan herba etnomedis di banyak negara seperti Indonesia, India, Vietnam, Cina, dan Jepang (Van et al, 2021). Beberapa studi farmakologi Alpinia telah dilaporkan memiliki berbagai bioaktivitas seperti aktivitas antikanker (Ibrahim, 2022;Lintao & Medina, 2021) aktivitas antioksidan, aktivitas antimikroba (Cruz et al, 2020;Ferdous et al, 2018), aktivitas anti inflamasi (Yu et al, 2020), dan aktivitas analgesik (Ahmed & Kumar, 2022).…”
Section: Pendahuluanunclassified
“…Genus Alpinia terutama dikenal sebagai tanaman dan herba etnomedis di banyak negara seperti Indonesia, India, Vietnam, Cina, dan Jepang (Van et al, 2021). Beberapa studi farmakologi Alpinia telah dilaporkan memiliki berbagai bioaktivitas seperti aktivitas antikanker (Ibrahim, 2022;Lintao & Medina, 2021) aktivitas antioksidan, aktivitas antimikroba (Cruz et al, 2020;Ferdous et al, 2018), aktivitas anti inflamasi (Yu et al, 2020), dan aktivitas analgesik (Ahmed & Kumar, 2022).…”
Section: Pendahuluanunclassified
“…Alpinia genus is mainly known as an ethnomedicinal plant and herb in many countries such as Indonesia, India, Vietnam, China, and Japan (Van et al, 2021). Several pharmacological studies of Alpinia have been reported, and they have various bioactivities such as anticancer activity (Ibrahim, 2022;Lintao & Medina, 2021), antioxidant activity, antimicrobial activity (Cruz et al, 2020;Ferdous et al, 2018), antiviral activity (Hatanaka et al, 2021;Narusaka et al, 2021;Zubair et al, 2021), antiinflammatory activity, anti-nociceptive activity (Yu et al, 2020), antiparasitic activity (Sulistyowaty et al, 2021), neuroprotection activity (Hashim et al, 2021;Mundugaru et al, 2018), antihypertensive activity (Moura et al, 2005) and analgesics activity (Ahmed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%